Motivational determinants among physicians in Lahore, Pakistan - Malik, Ahmad Azam; Yamamoto, Shelby; Souares-Coutant, Aurélia; Malik, Zeeshan; Sauerborn, Rainer (BMC health services research, 2010)
Human resource crises in developing countries have been identified as a critical aspect of poor quality and low accessibility in health care. Worker motivation is an important facet of this issue. Specifically, motivation among physicians, who are an important bridge between health systems and patients, should be considered. This study aimed to identify the determinants of job motivation among physicians, a neglected perspective, especially in developing countries.
Gesehen am 03.05.2023